1997
DOI: 10.1074/jbc.272.51.32606
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nuclear Transcription Factor NF-κB by Interleukin-1 Is Accompanied by Casein Kinase II-mediated Phosphorylation of the p65 Subunit

Abstract: In fibroblasts and hepatoma cells, interleukin-1 (IL-1) treatment results in the rapid nuclear accumulation of the transcription factor NF-B, present largely as p65 (RelA)/p50 heterodimers. It is well established that this process is dependent in large part upon the phosphorylation and subsequent degradation of the cytosolic inhibitor IB. We looked for other IL-1-induced modifications of NF-B components and found that, in both cell types, IL-1 stimulation led, within minutes, to phosphorylation of both NF-B p6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
3
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(150 citation statements)
references
References 53 publications
7
139
3
1
Order By: Relevance
“…Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis showed that CK2a is a candidate (Table I). Consistently, it was previously shown that CK2a associates with the BCR moiety of BCR-Abl (24,25), and CK2 phosphorylates p65 (10)(11)(12). Therefore, we hypothesized that CK2a associated with not only BCR-Abl but also BCR and that CK2a is a critical kinase for BCR-mediated inflammation development in vivo and in vitro.…”
Section: Formation Of the Bcr-ck2a Complex Is Required For Inflammatisupporting
confidence: 52%
See 1 more Smart Citation
“…Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis showed that CK2a is a candidate (Table I). Consistently, it was previously shown that CK2a associates with the BCR moiety of BCR-Abl (24,25), and CK2 phosphorylates p65 (10)(11)(12). Therefore, we hypothesized that CK2a associated with not only BCR-Abl but also BCR and that CK2a is a critical kinase for BCR-mediated inflammation development in vivo and in vitro.…”
Section: Formation Of the Bcr-ck2a Complex Is Required For Inflammatisupporting
confidence: 52%
“…CK2 forms a heterocomplex composed of two catalytic a subunits and two regulatory subunits (9). It was reported that CK2 phosphorylates p65 (10)(11)(12), an action critical for NF-kB-mediated transcription (13,14), although a detailed molecular mechanism of how CK2 regulates the transcription has not been shown.…”
Section: B Reakpoint Cluster Region (Bcr) Protein Is a Unique Kinasementioning
confidence: 99%
“…21). Thus far, inducible phosphorylation of RelA/p65 at serine residues 276 or 311 in the Rel homology domain or serine residues 468, 529, and 536 in the TD have been observed following exposure of cells to various NF-B-inducing agents, culminating in the modulation of nuclear localization, DNA-binding affinity, coactivator/corepressor association, and transactivation capacity (14,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Inducible phosphorylation of cRel was also detected in response to PMA, CD28, or TNF-␣ treatment of T cells (34 -36); phosphorylation of Ser 471 in the TD has been reported to be involved in TNF-␣-induced activation of cRel (34,35), whereas Ser 451 in the TD of murine cRel serves as a phospho-acceptor site, although the physiological function of this event remains to be elucidated (37).…”
mentioning
confidence: 99%
“…partie des kinases qui règlent la dégradation de IκB [26] et stimulent l'activité transcriptionnelle de NF-κB [27,28]. Le fait que le promoteur du gène de CK2α soit régulé par NF-κB permet d'envisager l'existence d'une boucle de rétrocontrôle positif conduisant à une surexpression concertée de CK2α et de NF-κB dans certains cancers [29].…”
Section: Ck2βunclassified